Auditoría interna de la propiedad, planta y equipo, y su efecto en el patrimonio de las empresas del sector farmacéutico - Alvarado Cerezo, Nixon Helixandro (2020)
This research entitled "Internal audit of property, plant and equipment, and its effect on the assets of companies in the pharmaceutical sector" where the impact on equity accounts due to changes in fixed assets was defined as a general objective of research (property, plant and equipment). To meet this objective and have an appreciation of what happens in this type of companies, the pharmaceutical company “FARMAHORRO S.A.” of the canton Vinces was chosen as a unit of study. A mixed type research approach was defined. The information was based on primary and secondary funetes of information, field research was applied to obtain directly from the company real information on the status of this accounting account based on a survey that focused on finding out different aspects of the accounting management of the company , in addition to the use of Internal Audit Techniques that allowed to deepen the existing shortcomings in the accounting process that occurs in the company..............